Techno-economic optimal planning of an industrial microgrid considering integrated energy resources - Ahmed, Mohammad Adel; Abbas, Ghulam; Jumani, Touqeer Ahmed; Rashid, Nasr; Bhutto, Aqeel Ahmed; Eldin, Sayed M. (Frontiers in Energy Research, 2023)
Microgrids have benefited energy systems by getting rid of the abundant use of traditional energy resources, replacing them with distributed generations (DGs). The use of DGs in microgrids not only provides clean and green energy but also reduces the gigantic losses in transmission and distribution lines. Widespread adoption of renewable energy in microgrids saves customers from high fuel prices and provides a sustainable replacement for future fossil fuel depletion. Microgrids have proven to be the latest and most advanced power systems due to their new capabilities to operate in both grid and isolated mode. Microgrids use multiple energy sources simultaneously which can offset the intermittent behavior of renewable energy sources. In this paper, an industrial microgrid is planned and optimized with an annual increase in load, which contains dispatchable generation, non-dispatched generation, and energy storage. In addition, to test the different behavior of a mi-crogrid operating independently or in grid-tied mode, four typical days are selected to show the load demand, and solar and wind energy forecast data for the entire year. The power output curves for each typical day are analyzed for every year in both stand-alone and grid-connected mode. Fur-thermore, to validate the feasibility of the microgrid the investment cost and operations costs are also calculated in the paper.